The Incorporation of the Corpus-Based Approach in the Teaching of Second Language Writing: A Case Study of Second Year L.M.D Students - BOUGHEZAL, Abdeldjalil (Journal of Human Sciences, 2020)
Writing is an indispensable skill in the realm of foreign language learning. Achieving a high level in such a skill is a complex undertaking. This complexity stems from the high standardised and conventionalised nature of writing, which entails awareness and mastery of the cognitive, linguistic, and psychological factors associated with such a process.This paper looks at the practicality and possibility of applying the Corpus-Based Approach to the teaching of L2 writing for second year L.M.D students. A corpus-oriented paradigm of teaching writing uses a variety of corpora as a method of instruction which would raise the students’ awareness of lexico-grammatical competence in terms of vocabulary, grammar, and the lexico-syntactic means of establishing textuality in terms of cohesion and collocation.